Pengaruh Efikasi Diri terhadap Keterikatan Kerja pada ASN di Kabupaten Sambas - Aji, Langgeng Banu; Damayanti, Devi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This research aims to investigate the influence of self-efficacy on the job engagement of civil servants (ASN) in Sambas Regency. The study used a quantitative approach, employing two scales: the modified Utrecht Work Engagement Scale (UWES) with 18 items and a self-efficacy scale with 12 items. Sampling was carried out using the cluster random sampling technique across 16 sub-districts in Sambas Regency, resulting in a total sample size of 378 respondents. Data analysis was performed using simple regression analysis. The research findings indicate a significance level of 0.000 (p << 0.05) with a correlation coefficient (R) of 0.806. This implies a highly significant positive influence of self-efficacy on work engagement among civil servants in Sambas Regency, with self-efficacy contributing 65% to work engagement among ASNs. Consequently, this study has a remaining effective contribution of 35% from unexamined factors. Based on the data analysis, it can be concluded that self-efficacy has a highly significant positive influence among civil servants in Sambas Regency.